2006
DOI: 10.1007/s00192-006-0226-3
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic prolapse and urinary incontinence in nulliparous college women in relation to paratrooper training

Abstract: The objective of this study was to determine whether paratrooper training is associated with pelvic support defects or urinary incontinence. Nulliparous women at The United States Military Academy were examined using the Pelvic Organ Prolapse Quantification System and completed a questionnaire regarding incontinence and exercise prior to undergoing summer military training. The exam and questionnaire were repeated following training. One hundred sixteen women completed the study (80.6%), 37 of whom had attende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 10 publications
0
25
0
Order By: Relevance
“…42,44,9 In three other studies, heavy work was associated with POP based on the POP-Q system, as was military paratrooper training. 28,43,45 …”
Section: Discussionmentioning
confidence: 99%
“…42,44,9 In three other studies, heavy work was associated with POP based on the POP-Q system, as was military paratrooper training. 28,43,45 …”
Section: Discussionmentioning
confidence: 99%
“…21,22 Based on this association, it could be hypothesised that vigorous physical activity may also be a risk factor. However, although two studies reported no association between current exercise or the self-report of past strenuous exercise and POP, 16,19 details of relevant data, such as the type of activity, frequency, duration and intensity, were not described.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the recently published integrated life span model, 6 it can be assumed that the development of POP includes predisposing factors (growth and development, genetic factors, connective tissue weakness, joint mobility), [7][8][9][10][11][12] inciting factors (childbirth, pelvic surgery) [12][13][14][15][16][17][18] and intervening factors (age-related changes, obesity, constipation, heavy occupational work, vigorous physical activity). 12,[14][15][16][17][18][19][20][21][22][23][24] Unfortunately, only a minority of these risk factors can easily be prevented.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 Women undergoing strenuous military activity such as heavy lifting or paratrooper training are more likely to have worsening of pelvic support. 25 The effect of these exposures over the long term as women transition to being veterans is unknown but could lead to increased rates of stress urinary incontinence and pelvic organ prolapse.…”
Section: Urogenital Healthmentioning
confidence: 99%